Association of different Co-morbidities as Predictors of Severe Pneumonia in under five Children - Parvin, Rukhsana; Mahmud, Shahabuddin; Saha, Dipanwita (Journal of Shaheed Suhrawardy Medical College, 2025)
Background: Pneumonia has been one of the leading causes of morbidity and mortality among children under five years of age for several decades. Pediatric patients with pneumonia often present with additional comorbidities that may delay recovery and increase overall morbidity. Therefore, we aimed to identify and analyze the risk factors and predictors associated with childhood pneumonia. Objectives: To find out the association of different co-morbidities as predictors of outcome of pneumonia patients in under five children. Methods: A total of admitted 292 patients with severe or very severe pneumonia with radiological findings were followed up and categorized into two groups, group A (n-178) with risk factors and the comorbidities and the other group B (n-122) without risk factors or co-morbidities. Both groups were compared prospectively to see the outcome. Probable predictors were found as prematurity, low-birth weight, absence of exclusive breast feeding, lack of immunization, episodes of respiratory disease in life time and comorbidities like congenital heart disease (VSD, ASD, PDA or other), Severe Acute Malnutrition (SAM), Down syndrome, Cerebral Palsy (CP), Nephrotic syndrome, Cystic Fibrosis, Duchene-Muscular Dystrophy (DMD), cleft lip or cleft palate. Out come or dependent variables were considered as duration of hospital stay (≥ 7days), use of 2nd line antibiotic, oxygen requirement\ (> 2 L), development of heart failure, use of digitalis and death if any. Study participants were provided standard treatment for pneumonia and both groups were compared prospectively to see the outcome. Results: Overall comorbidities had more in group-A, compared to group-B (66.9% vs. 10.5%) and on the contrary, absent of comorbidities had more in group-B, compared to group-A (89.5% vs. 33.1%). Severe Acute Malnutrition (SAM), heart failure, cleft palate, Down syndrome, VSD, prematurity, low birth weight, ASD and PDA in terms of comorbidity had significantly more in group-A compared to group-B children. Out of them VSD, Heart Failure, SAM, Down syndrome, prematurity and low birth weight were found to be significantly associated with group-A patients compared to group-B patients with Odd Ratios being 8.49, 7.09, 4.42, 3.65, 3.20 and 2.92 respectively by simple regression analysis. Conclusion: Early identification and management of co-morbidities in childhood pneumonia can help to prevent serious complications and reduce morbidity, thereby may lessen the hospital burden in low-income countries such as Bangladesh. J Shaheed Suhrawardy Med Coll 2024; 16(1): 33-38